Health status of adolescent school going children with special reference to waist hip ratio - Vasavada, Halak J.; Patel, Snehal V.; Patel, Purvi R.; Mehta, Heli S. (International Journal of Contemporary Pediatrics, 2020)
Background: A school is a key location for educating adolescents about health, hygiene and nutrition. Adolescence is period of critical development and transition. These changes have important implications for health. Aims and objectives of the stud was to study the role of WHR in nutritional assessment in adolescent school children and compare it with BMI as an assessment tool and to study nutritional status of municipal and private school. Methods: It was a cross sectional study conducted in 10-17-year-old school children in Ahmedabad, Gujarat. There were 2 private and 2 municipal schools selected randomly by purposive sampling. Child absent or not well on the day of study were excluded. Results: Incidence of obesity is 42.9% and 57.1% in municipal and private school respectively. Incidence of overweight is 47.2% and 52.8% in municipal and private schools respectively. (2.9%) adolescents had BMI range of 25-29.9 which is considered to be overweight. However, the percentage of overweight and obese was raised at 28% and 23.5% respectively when classified as per WHR. Conclusions: The difference between incidence of overweight and obesity in private and municipal schools were not statistically significant. A combination of increase BMI with increase WHR is a stronger indicator of increase health risk.